PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT INDOCEMENT TUNGGAL PRAKARSA TBK TAHUN 2014 – 2023 - Patma Sari Lubis; Muhamad Nurhamdi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Current Ratio and Debt to Equity Ratio on Return on Assets at PT Indocement Tunggal Perkasa Tbk for the period 2014 - 2023. This study uses Quantitative Methods. The analysis techniques used in this study are descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination, correlation coefficient, and hypothesis testing. Based on the results of the study, it shows that the Current Ratio partially has a significant effect on Return on Assets based on the t-test at a = 0.05, t count> t table (10.844> 0.05), Debt to Equity Ratio variables partially have a significant effect on Return on Assets based on the t-test at a = 0.05, t count> t table (7.576> 1.859), with a significant value of 0.000 <0.05. Simultaneously F test on df = (10 -2-1) = 7 can be determined f count > f table (77.099, > 4.737) with a significant value of 0.000 <0.05 then Ho is rejected Ha is accepted. It can be concluded that there is a significant influence on the current ratio and debt to equity ratio simultaneously on return on assets. The results of the determination coefficient test show the Adjusted R Square value of 0.944, then (KD = r2 x 100% = 0.944 x 100% = 94.4%) so it can be concluded that the Current Ratio (CR) and Debt to Equity Ratio (DER) have an effect of 94.4% on Return on Asset (ROA), while the remaining 5.6% is influenced by other variables not examined in this study.